The Islamic View of Christianity - Nasr, Seyyed Hossein (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
This paper aims at clarifying the traditional Islamic views of Christianity based on Qur’an and Hadith and the interpretations of these twin primary sources of Islam by Muslim religious authorities over the centuries. In light of the Qur’anic Christology, the paper presents a critical review of the Muslim understanding of Christian theology as well as its ethnic and religious practices. In particular, the paper discusses the traditional Islamic view of the Christian doctrine of Trinity and of Incarnation. A special reference is made to the view of Ibn ‘Arabi in the subject. The paper also discusses what the absence in Christianity of a divine law, the shari’ah , as understood in both Judaism and Islam, means to that religion particularly In terms of its capability to offer a life of equilibrium between the spiritual and the temporal for its ordinary believers. Also touched is the Muslim belief of abrogation of one divine revelation by a subsequent revelation. This belief has implications for the Muslim attitudes toward other religions, including Christianity. Finally, the paper discusses the major factors that have brought about changes, more often negative, in the Muslim-Christian relations in the modern world.